‘Before she ends up in a brothel’: Public Femininity and the First Actresses in England and the Low Countries - van Elk, Martine (Early Modern Low Countries, 2017)
This essay explores the first appearance of actresses on the public stage in England and the Dutch Republic. It considers the cultural climate, the theaters, and the plays selected for these early performances, particularly from the perspective of public femininity. In both countries antitheatricalists denounced female acting as a form of prostitution and evidence of inner corruption. In England, theaters were commercial institutions with intimate spaces that capitalized on the staging of privacy as theatrical. By contrast, the Schouwburg, the only public playhouse in Amsterdam, was an institution with a more civic character, in which the actress could be treated as unequivocally a public figure. I explain these differences in the light of changing conceptions of public and private and suggest that the treatment of the actress shows a stronger public-private division in the Dutch Republic than in England.